Parturient symphysio-fundal height and abdominal girth measurements to predict birth weight at Muhimbili Medical Centre, Dar es Salaam, Tanzania (Tanzania Medical Journal, 2007)
Birth weight is known to influence morbidity and mortality. Simple measures to predict birth weight before delivery would therefore be useful in order to plan a delivery. Maternal parturient symphysio-fundal height has been used to detect Low Birth Weight. This study aims at predicting the fetal weight using the maternal symphysio-fundal height and abdominal girth.A prospective study was done on 600 pregnant women admitted in labor. A detail anthropometric measurement was done and correlated with birth weight after delivery. Symphysio-fundal height and abdominal girth measured to the nearest centimeter positively correlated with birth weight. The coefficient of correlation was 0.74 and 0.69 respectively with a significance of p0.295). A formula was derived for the estimation of birth weight using these two parameters viz: Birth weight = Bo + B1 (Abdominal girth) + B2 (symphysio-fundal height) where B0 is a constant =2.61, B1 (partial regression coefficient) = 0.32 (Standard deviation 0.002) and B2 (partial regression coefficient) = 0.081 (Standard deviation 0.004).The sensitivity in detecting birth weight below 2 kg was 88.2% and the specificity was 84.3%. While the specificity for detecting birth weight above 3.8kg was 83.3% and a specificity of 68%. The Symphysio-fundal height and abdominal girth could predict the birth weight more closely than the gestational age. Keywords: Symphysio-fundal height, abdominal girth, parturient, prediction, birth weight. Tanzania Medical Journal Vol. 19 (1) 2004: pp.